1998
DOI: 10.1046/j.1365-2427.1998.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of both benthic and drift sampling techniques to assess tropical stream invertebrate communities along an altitudinal gradient, Costa Rica

Abstract: 1. Two sampling techniques were used to characterize invertebrate communities in eight, low‐order streams along an altitudinal gradient in Costa Rica that represents the last continuous tract of primary forest spanning such extremes in elevation (i.e. near sea level to 2900 m a.s.l.) along the Caribbean Slope of Central America. A standard Surber sampler was used to sample invertebrates on the stream bottom, and drift sampling nets were used to sample invertebrates drifting in the stream flow. 2. Sites were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 44 publications
3
52
2
Order By: Relevance
“…This result differs with data from temperate areas (Allan 1984, 1987, Allan et al 1988 where night drift densities can be up to 10× greater. However, this is not in agreement with previous studies of tropical streams where diel periodicity in drift was weak or nonexistent (Turcotte & Harper 1982, Pringle & Ramirez 1998, Jacobsen & Bojsen 2002, Rodriguez-Barrios et al 2007. Despite the overall findings, 2 ephemeropterans, Baetodes and Leptohyphes, showed diel periodicity.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…This result differs with data from temperate areas (Allan 1984, 1987, Allan et al 1988 where night drift densities can be up to 10× greater. However, this is not in agreement with previous studies of tropical streams where diel periodicity in drift was weak or nonexistent (Turcotte & Harper 1982, Pringle & Ramirez 1998, Jacobsen & Bojsen 2002, Rodriguez-Barrios et al 2007. Despite the overall findings, 2 ephemeropterans, Baetodes and Leptohyphes, showed diel periodicity.…”
Section: Discussioncontrasting
confidence: 93%
“…In tropical areas, recent studies have shown that diel drift patterns are only present on rivers with fish, while the absence of diel patterns has been reported in fishless rivers (Flecker 1992, Pringle & Ramirez 1998, Jacobsen & Bojsen 2002. In the tropics, drift is generally aseasonal (Pringle & Ramirez 1998, Ramirez & Pringle 2001, Jacobsen & Bojsen 2002, Rodriguez-Barrios et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies on the larval biology of such species have definitively demonstrated such larval drift (Holmquist et al, 1998;March et al, 1998;Benstead et al, 1999). Most of these species occur in tropical and subtropical stream habitats in which distances from the adult habitat to the sea are relatively short, i.e., a few to dozens of kilometers, e.g., Puerto Rico, other Caribbean and small oceanic Indo-Pacific islands; large islands (e.g., Japan, Taiwan) and continental locations relatively close to the sea (coastal stream systems in Costa Rica, e.g., Pringle & Ramirez, 1998;Covich, 2009).…”
Section: Transfer Of Larvae From Freshwater To the Seamentioning
confidence: 99%
“…In contrast to other studies [151], however, shrimps and crabs were relatively scarce in our samples. This is likely an artefact of our sampling technique, as benthic sampling generally underestimates the abundance of decapods [152], and shrimp of the genus Macrobrachium (particularly M. carcinus), Atya scabra, and crabs of the genus Avotrichodactylus can regularly be collected in non-sulphidic habitats using seines and baited traps (Tobler, personal observation).…”
Section: Aquatic Macroinvertebrate Communitiesmentioning
confidence: 99%